Efeito do diferimento sobre a produção e composição bromatológica do capim-marandu nos tabuleiros costeiros do Piauí - Rodrigues Júnior, Conrado Timbó (2013)
The use of different pasture is an alternative that may allow the production of "stockpiling" with yield and quality, reflecting positively on forage supply during food shortages. This technique is used in the preservation of forage dispensing investment in machines, implements, and storage structures, the main advantage of reduced production costs. The objective of this trial was to evaluate the environmental conditions of the coastal plains of Piauí, availability and chemical composition of Brachiaria brizantha. Palisade, subjected to different times of sealing for use in the dry season. The experiment was conducted at Embrapa Meio-Norte in the city of Parnaíba, Piauí. The experimental design was a randomized block design in a factorial 3 x 4, 3 times of postponement (March 23, April 19 and May 17) and 4 times of use (July 12, August 9, 6 September and October 4), with three replications. Forage availability was assessed for total dry mass, dry mass of green, agronomic characteristics such as the percentage of leaf blades, stem percentage over sheath, leaf / stem ratio, percentage of dead material, the relationship between material and living / dead material and height pasture the its nutritional value through the dry matter content of leaves and stems, and crude protein of leaves and stems, ether extract of the leaves and stems, neutral detergent fiber from the leaves and stems, acid detergent fiber from the leaves and stems, ash from leaves and stems. Combining forage availability with chemical composition, it is recommended as the best time of deferral the month of May, for use in September and October, ensuring a supply forage with adequate nutritional value to the conditions in the region of the coastal plains of Piauí.